The Excellence of Cocoa-Goat Integrated Farming in the Implementation of Zero Waste Concept - Ihda Fitriyah; Yuli Hariyati (SEAS (Sustainable Environment Agricultural Science), 2020)
The problem for farmers in Suruh Village is having two types of farming which are cacao-goat integrated system farmer and cacao-goat non-integrated system farmer. Cacao-goat integrated system conducts cacao farming with goat livestock while for the cacao-goat non-integrated system does not conduct goat livestock. Farmer's interest is different in conducting cacao farming system. The aim of cacao-goat integration system is obtaining manure as organic fertilizer by the expectation to save fertilization cost so that farmer's income with the cacao-goat integrated farming system will be different with non-integrated one because seen from the maintenance cost because of manure. In this study, we dig pattern analysis information of the cacao-goat integrated farming system to find out cacao-goat integrated system and income difference of cacao-goat integrated and non-integrated systems so that it aims to find out the pattern difference of cacao-goat integration farming The research result shows that cacao-goat integrated system by the utilization of cacao waste (bark, leaf), intercropped plant (avocado, cassava, stink beans) as the animal feed of goat). Goat livestock produces feces that can be used as cacao compost fertilizer after 12 months of fermentation. The average income of the cocoa-goat non-integration farmer is USD 1,184.91/Ha/Year, while for the cocoa-goat non-integration farmer has the average income of USD 854,673/Ha/Year. There is a significant difference between cacao-goat integrated farming income and cacao-goat non-integrated farming income.